Inventory Of Meat Randang Recipesin The City Of Pariaman - Ilma Ariyeniwinsah; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
The purpose of this study was to make an inventory of various kinds of meat randang recipes which include ingredients, spices, equipment and processing processes in Kota Pariaman. This research is motivated by the absence of data explaining the variety of meat randang recipes in Pariaman City and as a first step in maintaining the nation's culture in promoting traditional regional food as a tourist destination. This type of research is qualitative. Data collection techniques by means of observation, interviews, and documentation. Data analysis used in the field is reduction, presentation, drawing conclusions and verification. The results of this study were 12 recipes of beef randang in Kota Pariaman. Generally, the main ingredients used are beef and coconut milk from old coconut seasoned with wet spices, namely shallots, garlic, ground chilies, ginger, galangal, lemongrass, and dry spices, namely coriander, cloves, and nutmeg. And the leaves are lime leaves, turmeric leaves, and bay leaves. The tools used are plastic com, filter, cutting board, grinding stone and blender, stale frying pan, sanduak and stove, samba plate, cambuang and frying pan. Processing of spices is different from stove fuel and firewood.